A case of dermatofibrosarcoma protuberans of the scalp treated with surface mould brachytherapy - Hans, Raj; Singh, Sankalp; Arvind, Prince; Sarin, Arti; Semwal, Manoj K.; Vats, Pankaj (Journal of Contemporary Brachytherapy, 2023)
Dermatofibrosarcoma protuberans (DFSP) is a locally aggressive soft tissue tumor with a high propensity of local recurrence after surgery. Radiotherapy as an adjuvant therapy has been shown to reduce recurrent rates of this disease. Surface mould brachytherapy is an effective and safe modality for the delivery of radiotherapy in soft tissue tumors, though its utilization and popularity have decreased in recent years. Here, we presented a case of a recurrent DFSP of the scalp who was treated with surgery followed by adjuvant surface mould brachytherapy to avoid dose inhomogeneity likely to occur in this anatomic region with external beam radiotherapy in the absence of intensity-modulated radiotherapy. The treatment was delivered successfully with minimal adverse reactions, and the patient is disease-free at 18 months post-treatment with no treatment toxicity.